Risk factors influencing the construction projects in yemen from expert’s perspective - R. A., Bahamid; S. I., Doh; Mohamrned A, Al-Sharafi; A. R., Rahimi (2019)
This purpose of this study is to validate the important risk factors influencing the construction projects in a developing country of Yemen by using experts’ evaluations and literature review. These factors influence the project's quality, time and cost. The semi-structured interviews were employed through online means using thirteen experts to achieve the set objective. Depending on the expert’s overviews, out of 56 considered factors, 42 factors were assigned as the most related risk factors influencing the construction projects in Yemen. The obtained outcomes from this study can serve as the risk factors for building blocks in establishing a conceptual model to manage risks of the construction projects in Yemen.